Kształtowanie umiejętności redagowania tekstów na zajęciach języka polskiego jako obcego - Orłowska-Popek, Zdzisława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The author of the article, based on her own clinical experience of working with the deaf, presents the ways adults can learn to write texts in Polish as a foreign language. She proposes exercises to improve their text editing ability. She draws attention to the words of W. T. Miodunka „Editing written texts is in fact a work on the basics of language as a developed code” [2003: 221].